Design, synthesis and biological evaluation of phenol-linked uncialamycin antibody-drug conjugates. Issue 1 (1st January 2020) - Poudel, Yam B.; Rao, Chetana; Kotapati, Srikanth; Deshpande, Madhura; Thevanayagam, Lourdes; Pan, Chin; Cardarelli, Josephine; Chowdari, Naidu; Kaspady, Mahammed; Samikannu, Ramesh; Kuppusamy, Prakasam; Saravanakumar, Pon; et al.
Graphical abstract: Abstract: Uncialamycin is one of the structurally simpler and newer members of enediyne family of natural products. It exhibits highly potent activity against several types of bacteria and cancer cells. Described herein is a strategy for the targeted delivery of this cytotoxic agent to tumors using an antibody-drug conjugate (ADC) approach. Central to the design of ADC were the generation of potent and chemically stable uncialamycin analogues and attachment of protease cleavable linkers to newly realized phenolic handles to prepare linker-payloads. Conjugation of the linker-payloads to tumor targeting antibody, in vitro activity and in vivo evaluation are presented.